EDUCATION SYSTEM NEEDS TO INFORMATION TECHNOLOGY - Оноприенко, В. И. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
New aspects of the education systems caused by the unprecedented progress of information and communication technologies and globalization are considered through the pryzm of interrelated values of democracy and education.